Judge performance indicator evaluation system: improvement continues - Kulikov, O. (Науковий вісник Ужгородського національного університету. Серія Право, 2023)
This article is an analytical work where author investigates the possible directions of improvement of the existing methodological basis of the procedure for evaluation the competences and qualities of persons who will form the judicial corps in Ukraine. The main focus of the research is directed to the analysis of the indicators used to assess the professional and personal features of judges (candidates for the positions of judges), to the repeatability of such indicators, as well as to the validity of including one or another indicator in the appropriate set of indicators, which in their combination will give an answer to questions regarding the compliance of a judge (candidate for the position of judge) with one or another evaluation criterion. It should be noted that in previous works, the author has already begun to study from a similar angle such two important indicators of judge evaluation as indicators of «effectiveness of administration of justice» and «activities to increase the professional level». In this study, the author continues the analysis of indicators for the correctness of their assignment to one or another criterion, establishing their fair weight in the overall assessment of the competencies of a judge (candidate for the position of judge) and includes, in particular, among them such indicators as «integrity», «honesty «, «decency», «discipline», «understanding and compliance with rules and norms» and others. Analyzing the problem of repeating the same indicators within the scope of different sub-criteria, the author of the article tries to prove the point of view that the existing approach reduces the reliability of the relevant criteria, artificially overestimates or underestimates their weight in the overall evaluation of the abilities of a judge (candidate for the position of judge). As a result, the study proves the necessity of eliminating of the repetition of the same indicators and adjust their weight to the fair value. The final aim of the conducted analysis is to encourage the legislative and judicial branches of power to take actions and steps that would systematize the existing methodology for evaluating the performance of judges (candidates for the positions of judges) and would help more accurately identify useful features in candidates that will dfine the professional community of Ukrainians judges in the nearest future.